2020
DOI: 10.22515/shirkah.v5i1.276
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Underpricing in Islamic and Non-Islamic Shares on IPO

Abstract: This study aims at investigating the factors affecting the share’s underpricing in service companies of the Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) covering the period from 2011 to 2017. Compared to the precedent studies, this study provides an empirical comparison between Islamic and non-Islamic shares on 22 underpricing stock samples from 44 IPOs in Islamic service shares and 21 underpricing samples from 32 IPOs in non-Islamic service shares. This study adopts a multiple linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
4
0
3
Order By: Relevance
“…We contribute to studies on shariah IPOs in several ways. First, consistent with previous findings, we show that shariah compliance reduces information asymmetry, leading to lower compensation to investors (Barry and Jennings, 1993; Mohd-Rashid et al , 2018; Setya et al , 2020). Second, we find that shariah IPOs underperform benchmark and non-shariah IPOs in the long run.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…We contribute to studies on shariah IPOs in several ways. First, consistent with previous findings, we show that shariah compliance reduces information asymmetry, leading to lower compensation to investors (Barry and Jennings, 1993; Mohd-Rashid et al , 2018; Setya et al , 2020). Second, we find that shariah IPOs underperform benchmark and non-shariah IPOs in the long run.…”
Section: Introductionsupporting
confidence: 92%
“…The initial return (underpricing) for shariah-compliant firms was mainly explained by company size and type of offer, and the initial return for non-shariah-compliant firms was driven by risks (Rahim and Yong, 2010). However, Setya et al (2020) show that same fundamental factors, underwriter's and auditor's reputation, affect both shariah and non-shariah IPO underpricing in Indonesia setting. Overall, the evidence on the effect of shariah on IPO underpricing is still limited and tends to point toward inconsistent conclusions.…”
Section: Literature Reviewmentioning
confidence: 92%
“…In the most recent publication, Otoritas Jasa Keuangan (2021) reported that before the COVID-19 crisis, the Islamic stock market in Indonesia had experienced unprecedented growth, which shows by the increasing market capitalization. Besides, Setya et al (2020) also added that Indonesian Islamic stock demonstrated a significant expansion measured by the greater accumulation of company assets in sharia-compliant indexes.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of sample period is based on the data availability, moreover, this study aims to covering the crises period in order to ascertained the contribution of business cycle towards Islamic banks' profitability ratio during economic turmoil. Therefore, this study covering the subprime-mortgage in 2008, the Greek crisis in 2010, and the depreciation of IDR against USD in 2018 (Bank Indonesia, 2018; Setya et al, 2020).…”
Section: Methodsmentioning
confidence: 99%